Keragaman Budaya Pengasuhan Anak Usia Dini di Kalimantan Timur: Kajian Grounded Theory Keluarga Kutai, Banjar, Dayak - Fachrul Rozie; Wilda Isna Kartika; Tiara Nurhaliza; Risda Amalia; Muhammad Henry Gunawan (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2022)
The limited research studies on early childhood care culture in the tribal context in Indonesia have encouraged researchers to be interested in raising the issue of how early childhood care cultures in East Kalimantan. The purpose of this study is to narrate the culture of early childhood care across tribes (Kutai, Banjar, and Dayak) and the internalization process is reviewed the values adopted, internalization of character and are that is applied. The research method used in this study is grounded theory. Data collection was carried out through semi-structured interviews in 6 participants consisting of three experts and three families from Samarinda City. The question form is in the form of experience in early childcare that allows them to explore the answer in terms of cultural dimensions. Researchers also adopted a quality research code of ethics to disguise the identity of participants in a thematic data analysis approach. The results of the study concluded that the culture of early childhood care for kutai, Banjar and Dayak families in East Kalimantan was influenced by historical perspectives and internalization of parenting through habituation and tribal values as learning children's character at home. This is known in the practice of habituation in the home environment is consistently carried out by the family. In other words, the contribution of this study can be used as an empirical study of the culture of early childhood care based on tribal culture (ethnoparenting).